Design of an Osteonecrosis Experimental Model in Rats. Histomorphometric Study - Fontana, Sebastían (2021)
Fil: Fontana, Sebastían. Universidad Nacional de Córdoba. Facultad de Odontología. Cátedra de Fisiología; Argentina.